Analisis Kendala-Kendala Dalam Penerapan SMM ISO 9001:2008 di Madrasah Aliyah Negeri 3 Palembang - Muhammad Haikal Dhafier (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
The purpose of this study is to describe and analyze the constraints in implementing ISO 9001: 2008 QMS in MAN 3 Palembang referring to the concept of plan, do, check, action (PDCA), and its application to quality management principles, namely: 1) customerfocus ( Customer Focus) through the madrasah service survey, 2) analysis of constraints in applying the ISO QMS in MAN 3 Palembang is the focus on customers which isstudents through a madrasa service survey which is a matter of facilities in the classroom and student toilet. The research design is descriptive using a qualitative approach with interviews, documentation studies and observations. Data obtained from respondents through interview techniques, documentation studies, and observations regarding experiences, opinions, knowledge and other aspects to be collected, reduced, presented, and drawn conclusions to have meaning. Based on the results of data analysis and discussion it can be concluded as follows: 1) the implementation of the ISO 9001: 2008 Quality Management System through madrasa service surveys and internal quality audits that lead to continuous improvement and customer satisfaction, 2) obstacles in implementation are problems of infrastructure facilities in the classroom students for examplethe fan is broken and the projector is dead, and infrastructure problems in the student toilet are, the toilet lights are off and the door is loose, 3) the effort to overcome these problems is to fix it immediately.